Developing a Family Medicine Program in Jordan: appraisal of trainees and trainers and final assessment outcomes [version 4; peer review: 2 approved] - Safiya Virji; Lana Alhalaseh; Benjamin Colton; David Spitaels; Jiskoot van Ewijk, Marleen; Amjad Al Shdaifat; Birgitte Schoenmakers (MedEdPublish)
Introduction Curriculum development in medical education, particularly in family medicine, is essential for preparing healthcare professionals to meet evolving patient needs. This article examines the development of a Family Medicine program in Jordan, focusing on challenges, methodologies, and outcomes. Methods The curriculum was developed through collaboration between Jordanian and European universities, emphasizing core family medicine principles, evidence-based practice, and local context. Two cohorts of trainees participated in the one-year program, which used a 'whole task learning model' covering communication, clinical knowledge, and community health. Feedback was gathered through focus group interviews with trainers and trainees, and pre- and post-test data were analyzed to assess effectiveness in terms of exam outcome. Results Feedback indicated positive perceptions among trainers and trainees. Trainees valued the transition to Arabic-led lectures, improved primary care understanding, and trainer engagement. Strengths included evidence-based guidelines and patient interaction emphasis. Areas for improvement included more face-to-face training and practical opportunities. Trainers suggested enhancing practical skills training and increasing Arabic materials. Both cohorts showed significant improvement on test scores. Challenges such as non-participation and cheating highlighted the need for regular attendance and academic integrity. Conclusion The research underscores the importance of feedback from trainees and trainers in curriculum development. Continuous improvement, comprehensive assessment, and prioritizing linguistic and cultural relevance are crucial for enhancing primary care delivery in Jordan.